Estimation of heterosis in yield and yield attributing traits in single cross hybrids of maize - Sharma, Hari Prasad; Dhakal, Krishna Hari; Kharel, Raju; Shrestha, Jiban (Journal of Maize Research and Development, 2016)
A field experiment was conducted at National Maize Research Program, Rampur, Chitwan, Nepal during winter season from 6th October, 2015 to 5th March 2016 to estimate different heterosis on single cross maize hybrids . Thirteen maize hybrids were tested randomized complete block design with three replications. Hybrid namely RML-98/RL-105 gave the highest standard heterosis (57.5%) for grain yield over CP-666 followed by RML-4/NML-2 (32.6%), RML-95/RL-105 (29%) and RML-5/RL-105 (20.6%). The hybrid RML-98/RL-105 produced the highest standard heterosis (75.1%) for grain yield over Rajkumar followed by RML-4/NML-2(50.2%), RML-95/RL-105(46.6%), RML-5/RL-105 and (35.7%). Mid and better parent heterosis were significantly higher for yield and yield attributes viz. ear length, ear diameter, no of kernel row per ear, no of kernel per row and test weight. The highest positive mid-parent heterosis for grain yield was found in RML-98/RL-105 followed by RML-5/RL-105, RML-95/RL-105, and RML-4/NML-2. For the grain yield the better parent heterosis was the highest in RML-98/RL-105, followed by RML-5/RL-105, RML-95/RL-105, and RML-4/NML-2. These results suggested that maize production can be maximized by cultivating hybrids namely RML-98/RL-105, RML-5/RL-105, RML-95/RL-105, and RML-4/NML-2.